Photochemistry and Photophysics of Shinorine Dimethyl Ester1. (2nd March 2018) - Orallo, Dalila E.; Fangio, María Florencia; Poblet, Martin; Carignan, Mario O.; Bernal, Luis; Carreto, José I.; Bertolotti, Sonia G.; Churio, María Sandra
Abstract: The photostability and photophysical properties of the dimethyl ester of the mycosporine‐like amino acid shinorine have been experimentally evaluated in aqueous solution and in the presence of direct micelles prepared with a cationic or an anionic detergent, respectively. In comparison with shinorine, the ester molecule increases the photostability, the fluorescence quantum yield and the fluorescence lifetime in water as well as in the micellar solutions. The effects are more pronounced in sodium dodecyl sulfate solutions and suggest that the electrostatic attractions with the micellar interface contribute to limit the movement of the molecules and influence the relative rate of their deactivation channels. However, the predominance of the nonradiative decay is maintained together with the UV photoprotective ability of this atypical mycosporine species. Abstract : Modifications in the substitution pattern of mycosporine‐like amino acids and the characteristics of the media affect their photophysicochemical behavior. Transformation of natural shinorine by methylation of the carboxylic groups enhances its photostability and fluorescence decay in aqueous solutions and in the presence of anionic micelles.